THE IMPLICATIONS OF ADVERSE CHILDHOOD EXPERIENCES FOR THE PROFESSIONAL REQUIREMENTS OF SOCIAL WORK - Glynnis Dykes (Social Work/Maatskaplike Werk, 2011)
Coombes and Anderson (2000:281) assert that the “extent and incidence” of adverse childhood experiences (ACEs) in families of origin of social workers have increasingly become the focus of research. Their research focused on six social workers who are adult children of alcoholic families. Olson’s (2006) research confirmed a high incidence of sexual and emotional abuse reported by the social work participants. This particular finding resonated with an earlier study by Black, Jeffreys and Hartley (1993), which had found that social work students report a high incidence of childhood trauma. Similarly, Earle (2008) studied early life experiences of social work students at the Universities of Limpopo and Stellenbosch. Although Schenck’s (2009) research focused on the socio-economic circumstances of fourth-year social work students at the University of South Africa (Unisa) that impacted on their throughput rate, it also revealed traumatic childhood experiences. Tshiwulla (2007) found that students at the University of the Western Cape felt poor in a self-damaging way. In all three South African studies a high proportion of students reported early traumatic experiences. In addition, in Earle’s (2008) study social work educators revealed their concern regarding the ethical behaviour of social work students, which appears to be affected by ACE.